The hidden gallery - Wood, Maryrose (Wood, Maryrose. Incorrigible children of Ashton Place, 2011)
Fifteen-year-old Miss Penelope Lumley, a governess trained at the Swanburne Academy for Poor Bright Females, takes the three Incorrigible Children of Ashton Place to London, England, and learns they are under a curse.